Fekete-Szeg¨o Functional of Classes of Analytic Functions Involving the q-Derivative Operator - Aini Janteng; Andy Liew Pik Hern; Rashidah Omar (2020)
Let A denote the class of functions which are analytic in the open unit disc U = {z ∈ C : |z| < 1}. In this paper, we introduce new classes of analytic functions involving q-derivative operator defined on U. Furthermore, we obtain the Fekete-Szeg¨o functional for functions f(z) belongs to these classes.